REVIEW STATUS PANEL SURYA DI INDONESIA MENUJU REALISASI KAPASITAS PLTS NASIONAL 6500 MW - Neli Lestari, Ni Made; Satya Kumara, I Nyoman; Dwi Giriantari, Ida Ayu (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i01.p4, 2021)
PLTS is a power plant that converts sunlight energy into electricity using photovoltaic technology. Solar panels play an important role in PLTS, because solar panels capture solar radiation then convert it into electrical energy. The development of solar panel technology is the key to support the development of PLTS. This article reviews about the development of solar panels in Indonesia as an important component to support the development of national solar power plants towards a capacity of 6500 MW by 2025. The review will be carried out on various aspects of solar panels including the national solar panel industry, solar panels available in the domestic market, and the availability of various panels. Data is obtained from the national panel industry, the PLTS project, the PLTS user association, the national EPC, the Ministry of Energy and Mineral Resources, and the national solar panel vendor. The survey result shows there are 241 panels, both local and foreign production. Panel capacities vary from 5 Watt to 500 Watt and panel voltages are available from 12 Volt, 24 Volt and 48 Volt. Based on the survey, it is also obtained the average of Rp/Wp is Rp.18,853/Wp and the average of W/m2 is 159,46 W/m2. Increasing solar panel production can be done by providing incentives to solar panel producers in the form of product purchase guarantees and incentives to develop new factories. Information regarding the current status of solar panels in Indonesia is expected to be a quick reference for people or institutions that need it, and can be used as an introduction to research and application of PLTS in Indonesia.